Retrospective study of Dengue Fever (DF) and Dengue Hemorrhagic Fever (DHF) patients at University Malaya Medical Center, Kuala Lumpur, Malaysia in the year 2005 - Jamaiah, I.; Rohela, M.; Nissapatorn, V.; Hiew, F.T.; Mohammad Halizam, A.; Noor Liani, H.; Siti Khairunnisaak, A.R. (SEAMEO Regional Tropical Medicine and Public Health Network, 2007)
The aim of this retrospective study was to determine the number of dengue fever (DF) and dengue hemorrhagic fever (DHF) cases admitted to University Malaya Medical Center (UMMC) in the year 2005 together with their clinical presentations and epidemiology. The data for 2005 was collected from the medical records department of UMMC. A total of 1,279 cases were admitted in 2005 with DF (81, n=1,040) and DHF (19, n=239). January had the greatest number of cases of DF and DHF (22, n=281) and April had the least (4, n=49). The greatest number of DF cases (38, n=392) were seen in the 20-29 year age group, while the greatest number of DHF cases (32, n=76) were in the 10-19 year age group. In regard to race, the greatest number of cases were seen in Malays (48, DF; 49, DHF). Males were more commonly infected than females. The majority of patients infected were students (30, n=385). All patients with DF and DHF presented with fever. The symptoms reported included nausea and vomiting, joint pain, gum bleeding and dehydration. The mean value hemoglobin, white blood cell count and platelet count were 14.4 g/dl, 4 x103/dl, 75 x106/dl for DF and 15.1 g/dl, 4 x103dl,52x106/dl for DHF. The majority of patients were treated with hydration therapy. There were three deaths reported, caused by dengue shock syndrome (DSS).